The Influence of Additives on the Rheological and Sedimentary Properties of Magnetorheological Fluid - Zhang, Xiangcheng; Liu, Xiaotong; Ruan, Xiaohui; Zhao, Jun; Gong, Xinglong (Frontiers in Materials, 2021)
In this research, the influence of surfactant on the rheological and sedimentary properties of the magnetorheological fluid (MRF) was tested and analyzed. The surfactants were stearic acid, sodium dodecyl sulfate (SDS), and their mixture, respectively. The MRF was composed of carbonyl iron particle, liquid paraffin, silicone oil, graphite particle, bentonite, stearic acid, and SDS. The experimental results indicated that the rheological properties of the MRF were mainly influenced by the mass fraction of carbonyl iron particle. When the mass fraction of carbonyl iron particle and surfactant was the same, the shear stress of MRF with stearic acid was larger than that of MRF with SDS, and the maximum increment was 73.81%. When the mass fraction of carbonyl iron particle was 40%-50%, the shear stress of MRF increased firstly and then decreased with the increasing of the external magnetic flux density. When the mass fraction of carbonyl iron particle was 60%-70%, the shear stress of MRF firstly increased and then kept stable with the increasing of the external magnetic flux density. The results indicated that the sedimentary property of MRF with the mixture was better than that of MRF with stearic acid or SDS. The settling rate of MRF with the mixture increased 91.53% when compared with samples with other additives.